Paro, pobreza, estado y familia en España, 1993 - Carabaña Morales, Julio; Salido Cortés, Olga (Cuadernos de Relaciones Laborales, 2007)
This paper is devoted to the study of the economic consequences of unemployment. We try to quantify the role played by the State, the household and the family in its remedy. Against the extended belief that unemployment is a phenomenon that hits mainly individuals, here we stress the idea of its “domestic” nature. We first take the point of view of the individual and estimate the contributions of the State, the household and the extended family to the individual income of the jobless. The family contributes little, and the State less than the household, although better targeted against poverty. From a domestic perspective, most of the disposable income of the jobless comes from the work of other household members and most of the rest from public transfers to other household members. All together, in 1993 unemployment was in Spain a minor cause of poverty, having raised its level from 19% to 23% of the working age population. Our results also give a negligible role to non-domestic kinship and suggest that the role of the household as a buffer for social conflicts has been at least exaggerated.